Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

2. Use the Factor Theorem to determine whether g(x) is a fac tor of p(x) in each of the following cases: (i) p(:r) = 23!1 + x2 - 2x - 1, g(x) = :r + 1 (ii) p(x) "" r3 + 3z2 + 3x + 1, g(:r) = :r + 2 (iii) p(x) = r3 - 4x2 + x + 6, g(:r) = x - 3.

2. Use the Factor Theorem to determine whether g(x) is a fac tor of p(x) in each of the following cases:
(i) p(:r) = 23!1 + x2 - 2x - 1, g(x) = :r + 1
(ii) p(x) "" r3 + 3z2 + 3x + 1, g(:r) = :r + 2
(iii) p(x) = r3 - 4x2 + x + 6, g(:r) = x - 3.

Grade:12th pass

1 Answers

Pawan Prajapati
askIITians Faculty 8741 Points
8 months ago
(i) Ifg(:r) is a factor of p(x). then p(- 1) = 0. Now, p(- 1) • - 2 + 1 + 2 - 1 = 0. Hence, g(:r) is a factor of p(%). (ii") Ifg(x) is a factor of p(x), then p(- 2) = 0. Now, p(- 2) = -.8 + 12 - 6 + 1= - 14 + 13 = -1¢ 0. Hence, g(:r) is not a factor of p(.%). (iii") Ifg(:r) is a factor of p{x), then p(3)' = 0. Now, p(3) = 27 - 36 + 3 + 6 = 36 - 36 = 0. Hence, g(:r) is a factor of p(x).

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free